Ameliorating potential effects of natural biological formulations and biostimulants on plant health and quality attributes in coriander-fenugreek intercropped strawberry (Fragaria × ananassa Duch.) - Priya Thakur; Pramod Kumar; CL Sharma; Uday Sharma; Nisha Sharma; Tanzin Ladon (BMC Plant Biology)
Abstract The present study documented the effect of bio-organics in legume intercropped strawberry cv. Camarosa during the years 2022 and 2023. Bio-organic fertilizer inputs included were Jeevamrit (JV), Ghan-Jeevamrit (GJ) and Azolla. Coriander-Strawberry-Fenugreek as intercropping system was adopted. The treatments comprised were T1: GJ at 100 g/m2 + JV at 10% +Azolla at 200 g/plant, T2: GJ at 150 g/m2 + JV at 10% +Azolla at 200 g/plant, T3: GJ at 100 g/m2 + JV at 20% +Azolla at 200 g/plant, T4: GJ at 150 g/m2 + JV at 20% +Azolla at 200 g/plant, T5: GJ at 100 g/m2 + JV at 10% +Azolla at 250 g/plant, T6: GJ at 150 g/m2 + JV at 10% +Azolla at 250 g/plant, T7: GJ at 100 g/m2 + JV at 20% +Azolla at 250 g/plant, T8: GJ at 150 g/m2 + JV at 20% +Azolla at 250 g/plant, T9: GJ at 150 g/m2 + JV at 20% as per SPNF, T10: Farmyard manure (100% N basis) and T11: Recommended dose of N: P:K (80:40:40 kg/ha) as control. Application of bio-stimulants at 50 g/plant and AM fungi @ 20 g/ plant was applied uniformly in treatments T1–T8. One month after transplanting, T3 showed positive influence on vegetative growth traits of strawberry plantlets. Minimum number of days taken to flower, maximum duration of flowering (142) and number of flowers (51) were also recorded. This treatment application also observed maximum fruit yield (677.93 g/ plant) and yield efficiency (7.91 g/cm2 of leaf area) compared to all other bio-organic combinations applied. Post harvest soil chemical indicators were also significantly influenced except pH and electrical conductivity compared to FYM (100% N equivalence) and Recommended dose of fertilizers (RDF) of NPK (80:40:40 kg/ha). Microbial biomass in terms of total bacteria, soil fungi, actinobacterial count, phosphorous solubilizing bacteria, AM spore population, Azotobacter count and Soil enzymatic activity of phosphatase and dehydrogenases showed a steady rise after application of GJ @ 100 g/m2 + JV @ 20% + Azolla @ 200 g/plant. In addition, overall increase of the yield of coriander and fenugreek compared to FYM (100% N equivalence) and RDF of NPK (80:40:40 kg/ha) was recorded. The positive influence both on leaf and fruit NPK contents were also recorded when plantlets were supplemented with GJ @100 g/m2 + JV@ 20% + Azolla @ 200 g/plant. This study inferred that application of bio-organic inputs sources which can boost up cropping behavior, post harvest soil indicators, native microbial properties and enzymatic activity in rhizosphere, and thus can have the potential to improve crop resilience and soil productivity on sustainable basis.